Isolation and Characterization of Violacein from an Antarctic Iodobacter: A Non-Pathogenic Psychrotolerant Microorganism - Encina-Rojas, M; Paez-Collio, M; Paez-Collio, M; Blamey-Alegria, J (Springer, 2020)
Violacein is an intensely purple pigment synthesized by various genera of bacteria that has been discovered to have a wide range of interesting biological activities which range from anticarcinogenic to antibacterial. One of the hindrances for its real-life application is that the first microorganisms found to produce the compound may act as opportunistic pathogens. Here, we report the isolation and characterization of violacein from a non-pathogenic Antarctic Iodobacter strain. Its anti-microbial properties were also tested. The method proposed here for the purification of violacein shows high yields, indicating that this Antarctic microorganism could be a valuable source for this important pigment. This is the first characterization of violacein from an Antarctic Iodobacter strain and here we also present a viable method to obtain this pigment for potential biotechnological applications. © 2019, Springer Japan KK, part of Springer Nature.